PENGARUH FAKTOR BUDAYA, SOSIAL, PRIBADI DAN PSIKOLOGI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN - Mira Shelviana; Marjam Desma Rahadhini; Edi Wibowo (Universitas Slamet Riyadi, 2020)
The purpose of this study was to: 1) Analyze the significance of the influence of cultural factors on purchasing decisions 2) Analyze the significance of the influence of social factors on purchasing decisions 3) Analyze the significance of the influence of personal factors on purchasing decisions 4) Analyze the significance of the influence of psychological factors on purchasing decisions 5) Analyze factors which has the most dominant influence on purchasing decisions. This research is a survey with the Timlo Sastro Solo consumer population in Surakarta. Research sample of 100 people with accidental sampling technique. Data collection techniques use questionnaires, interviews and literature studies. Data analysis techniques use multiple linear regression analysis, t test, F test and coefficient of determination. The results showed that cultural factors, social factors, personal factors and psychological factors had a significant effect on the purchase decision of Timlo Sastro Solo. Cultural factors are variables that have a dominant effect on the purchasing decisions of Timlo Sastro Solo.